Inclusive leadership : equity and belonging in our communities - Barnes, Joanne; Stevens, Michael J.; Ekelund, Bjørn Z.; Perham-Lippman, Karen (Building leadership bridges., 2023)
Diversity, Equity, Inclusion, Belonging, and Access (DEIB/A) represent essential features of the human side of any organization or community. To fulfil dreams and aspirations and to foster collective flourishing, inclusive leadership is vital. Making this happen is the central challenge and the focus of this collection of chapters comprising a wide variety of authors and perspectives. Inclusive Leadership speaks to the human side of organization and communities. Both practitioners and academics provide insights that broaden our traditional view of diversity issues into a perspective focused on better understanding the theory and practice of inclusive leadership. Chapters include empirical work, ground-breaking ideas, and practical tools from different sectors and parts of the world fundamental to a rich view of DEIB/A. Inclusive Leadership is essential reading for leaders aiming to create a space where individuals find genuine belonging.